The management of renal candidiasis in the newborn - Üçsel, Raif; Çoban, Asuman; Metin, Fazilet; Yücer, Gül; Ziylan, Orhan; Tonguç, Erdem; Bilge, Ilmay; Rouzbeksalah, Keyhan; Can, Gülay (The Turkish Journal of Pediatrics, 1996)
Renal candidiasis in the neonate is encountered infrequently. We report a newborn with ichthyosis, who during the hospital course had five episodes of culture-proven sepsis, probably due to skin lesions. For these infections various antibiotic combinations were used. During the therapy of the last sepsis attack, unilateral hydronephrosis developed secondary to renal candidiasis. Percutaneous nephrostomy with amphotericin B irrigation, coupled with five weeks of intravenous amphotericin B therapy was successful. We believe that with this approach the mortality and morbidity of renal candidiasis could be reduced.